Ulayat, Costum and Conflict: A Delicate Balance in Tiku Limo Jorong Community - Indrizal, Edi; Ermayanti, Ermayanti; Nurti, Yevita; Irwandi, Ade; Ramdesta, Andry (Universitas Pendidikan Ganesha, 2025)
This paper explains the agreement to hand over customary land as HGU for PT AMP Plantation which has conflict vulnerability. In 1994, the process of handing over customary land by Ninik Mamak Nagari Tiku Limo Jorong to the local government and made HGU by PT AMP Plantation for oil palm plantations. In the process there is an agreement agreed upon, namely the issue of the division of core land (70%) and plasma (30%) and compensation money (siliah jariah). So, the community demanded that this be realised. But over time, conflicts occurred both internally in the community and with the company. The approach uses descriptive methods with data collection in-depth interviews and observations. Infrorman was drawn using mixed techniques, namely purpose sampling and snowball. The results show that the conflict that occurred has been completed with a long process from 2000 until now. However, it is highly susceptible to future conflicts. The long conflict was influenced by two factors, which were the dualism factor of Ninik Mamak and the delay of the company to find a new agreement. Therefore, the balance made from the agreement letter is very vulnerable, because customary land is still bound to the community and the company even though it has become HGU.